2014
DOI: 10.5937/sjm9-4314
|View full text |Cite
|
Sign up to set email alerts
|

10.5937/sjm9-4314 = Impact of environmental factors on the efficiency of tax organizations

Abstract: Global financial and economic crisis has brought to the fore the need for assessing public sector performance. Improving the functioning of public sector and enhancing the efficiency of public administration constitute measures taken by governments to cushion the effect of the crisis on their country economies. Equal distribution of public expenditure and taxation countrywide is essentially important for social cohesion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
(20 reference statements)
0
8
0
1
Order By: Relevance
“…() point out, most have been published in relatively low profile journals. In those works we notice that the evaluated units are quite heterogeneous, including studies that analyze the activities of real tax offices (Moesen and Persoons, ; Barros, , , ; Førsund et al., , ; Katharaki and Tsakas, ; Tsakas and Katharaki, ; Fuentes and Lillo‐Bañuls, ), as well as others that analyze the performance of regions (Jha and Sahni, ; Jha et al., ; González and Miles, ; Esteller, 2003; Barrilao and Villar, ), municipalities (Mattos et al., ), or tax jurisdictions (Ruy and Lee, ). There are even papers assessing the performance of national revenue services from a comparative viewpoint (Alm and Duncan, ; Savić et al., ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…() point out, most have been published in relatively low profile journals. In those works we notice that the evaluated units are quite heterogeneous, including studies that analyze the activities of real tax offices (Moesen and Persoons, ; Barros, , , ; Førsund et al., , ; Katharaki and Tsakas, ; Tsakas and Katharaki, ; Fuentes and Lillo‐Bañuls, ), as well as others that analyze the performance of regions (Jha and Sahni, ; Jha et al., ; González and Miles, ; Esteller, 2003; Barrilao and Villar, ), municipalities (Mattos et al., ), or tax jurisdictions (Ruy and Lee, ). There are even papers assessing the performance of national revenue services from a comparative viewpoint (Alm and Duncan, ; Savić et al., ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…González and Miles () are the only researchers to use bootstrapping techniques to achieve more robust results, whereas the others are mainly concerned with exploring the possible influence of different environmental or exogenous factors on efficiency measures using second‐stage models. This approach involves estimating a censored Tobit regression including the efficiency indices estimated in the first stage as a dependent variable and the exogenous factors as explanatory variables (Moesen and Persoons, ; Barros, ; Katharaki and Tsakas, ; Mattos et al., ; Tsakas and Katharaki, ; Savic et al., ). The main problem of this approach is that it relies on the separability condition between the input/output space and the space of exogenous variables, that is, assuming that these factors have no influence on the attainable set, which may not hold in some situations .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moesen and Persoon () used the non‐parametric free disposal method and DEA to evaluate the productive efficiencies of 289 local tax offices in Belgium and found that tax office efficiency was directly related to tax office size. Tsakas and Katharaki () used DEA with bootstrap methods to examine the performance of 35 tax offices in Greece. The DEA model was also used in Barros's () study to evaluate the efficiencies of applied mechanisms and asset allocation in tax offices in Lisbon, Portugal.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Continuing their 2010 study, Tsakas and Katharaki (2014) examined the performance of tax authorities in Greece, based on data obtained from a sample of 35 tax offices in the period from [2001][2002][2003][2004][2005][2006]. Performance was assessed using the DEA method (BBC output-oriented model) and bootstrap.…”
Section: Literature Reviewmentioning
confidence: 99%